ETHNOPHARMACOLOGICAL STUDIES ON THE MEDICINAL PLANTS USED BY KANI TRIBES OF THACHAMALAI HILL, KANYAKUMARI, TAMILNADU, INDIA - Divya, V. V., Karthick, N. and Umamaheswari, S. (I.J.A.B.R, 2013)
An ethnobotanical survey was carried out among Kani tribes of Thachamalai hill, Kanykumari Wild life sanctuary TamilNadu. The present paper documents traditional knowledge of Kani tribes about medicinal plants along with their family names and mode of preparation and uses .Information was collected through regular visits and interviews with llocal people and traditional healers .The study offer information about 106 plants which are used to treat around 25 diseases. Kani tribes of Thachamalai hill have rich knowledge on traditional remedies which will be useful to divulge new drugs for mankind.